The presence of Chlamydia phage PhiCPG1 capsid protein VP1 genes and antibodies in patients infected with Chlamydia trachomatis - Ma, Jingyue; Liu, Yuan; Liu, Yuanjun; Li, Lingjie; Hou, Shuping; Gao, Xibo; Qi, Manli; Liu, Quanzhong (Acta biochimica Polonica, 2016)
Chlamydia phage PhiCPG1 has been found in Chlamydia caviae in a guinea pig model for inclusion conjunctivitis, raising the possibility that Chlamydia phage is also present in patients infected with C. trachomatis (Ct). In the present study, we assayed for presence of Chlamydia phage capsid protein VP1 genes and antibodies in 84 non-Ct controls and 206 Ct patients using an enzyme-linked immunoassay (ELISA), followed by verification with Western blot. None of the subjects were exposed to an antibiotic treatment or had a C. pneumoniae infection. The VP1 antibody test was positive in both, the ELISA and Western blot assay, in 4 Ct patients. PCR amplification experiments revealed presence of the VP1 gene in 5 Ct patients. The results suggest that Chlamydia phage capsid protein VP1 may exist in some Ct patients.